Sperm parameters, DNA integrity, and protamine expression in patients with type II diabetes mellitus. (3rd April 2021) - Imani, M.; Talebi, A. R.; Fesahat, F.; Rahiminia, T.; Seifati, S. M.; Dehghanpour, F.
Abstract: Diabetes Mellitus (DM) is the most common endocrine disorder affecting many human physiological systems and tissues, including the reproductive organs in men. The age of individuals suffering from this disease has been falling rapidly in recent years. This study compared the effect of DM on sperm parameters, chromatin quality, and apoptosis, as well as the expression profile of protamine genes in men with and without DM using molecular and cytochemical assays. Sixty semen samples from the control group ( N  = 30) and case group ( N  = 30) were collected. There was a significant decrease in the percentages of sperm parameters in cases versus the controls ( p ˂0.05). Despite significantly higher percentages detected in spermatozoa with AB +, CMA3 +, and TUNEL +, no change was demonstrated regarding protamines mRNA levels, as well as the P1/P2 ratios in cases in comparison with controls. In contrast, significant positive correlations were found between the quantity of P1 and P2 transcripts ( r  = 0.944, p  < .001). The data indicated that DM not only caused a decrease in the quality of sperm parameters but also affected the sperm maturation process by increasing the substantial implications in the sperm DNA/chromatin levels of DM patients. IMPACT STATEMENT: What is already known on this subject? Diabetes Mellitus (DM) is a chronic metabolic disorder affecting many human physiological systems and tissues, including the reproductive organs in men. The age of individuals suffering from this disease has been falling rapidly in recent years. What do the results of this study add? We found that DM not only caused a decrease in the quality of the sperm parameters, including motility and concentration, and an increase in morphological abnormalities but also affected the sperm maturation process by increasing the substantial implications in sperm DNA/chromatin levels of DM patients. Despite there being no significant difference in the mRNA levels of protamines between the two groups, our findings showed a positive correlation between the mRNA levels of P1 and progressive sperm motility. What are the implications of these findings for clinical practice and/or further research? Based on the results of this study, chromatin and DNA assessments can have important implications for increasing fertility, as complementary tests, in combination with routine laboratory tests. Since sperm standard parameters are not capable of examining the condition of the sperm nucleus, men with abnormal sperm DNA can also have normal spermatogram, and diabetes is prevalent in reproductive age.